Costs of typhoid vaccination for international travelers from the United States - Heesoo Joo; Brian A. Maskery; Louise K. Francois Watkins; Joohyun Park; Kristina M. Angelo; Eric S. Halsey (Travel Medicine and Infectious Disease)
In the United States, typhoid vaccination is recommended for international travelers to areas with a recognized risk of typhoid exposure. Using MarketScan® Commercial Database from 2016 through 2022, we estimated typhoid vaccination costs by route (injectable vs. oral) and provider setting (clinic vs. pharmacy). Of 165,930 vaccinated individuals, 99,471 received injectable and 66,459 received oral typhoid vaccines, with 88 % and 17 % respectively administered at clinics. Average costs for injectable vaccination were $132.91 per person [95 % confidence interval (CI): $132.68–$133.13], with clinic and pharmacy costs at $136.38 [95 % CI: $136.14–$136.63] and $107.45 [95 % CI: $107.13–$107.77], respectively. Oral vaccination costs averaged $81.23 per person [95 % CI: $81.14–$81.33], encompassing $86.61 [95 % CI: $86.13–$87.10] at clinics and $80.14 [95 % CI: $80.09–$80.19] at pharmacies. Out-of-pocket costs comprised 21 % and 33 % of total costs for injectable and oral vaccinations. These findings may inform clinical decision-making to protect international travelers’ health.